Quantitative Approaches in Logistics and Supply Chain Management Proceedings of the 8th Workshop on Logistics and Supply Chain Management, Berkeley, California, October 3rd and 4th, 2013 - Sebastian, Hans-Jürgen.; Kaminsky, Phil.; Müller, Thomas; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This contributed volume presents selected research papers from the 8th workshop on Logistics and Supply Chain Management, which was held in October 2013 in Berkeley, California. It focuses on the topical issue of quantitative approaches in logistics and supply chain management, mainly covering facility location and location routing; vehicle routing and scheduling; courier, express and parcel service network design; healthcare logistics as well as logistics risk management. The target audience primarily comprises research experts and practitioners in the field, but the book will also be beneficial to graduate students.
Modeling Mixed Load School Bus Routing -- Some Numerical Studies for a Complicated Hub Location Problem -- Maintenance Enterprise Resource Planning: Information Value among Supply Chain Elements -- Strategic Planning of Optimal Networks for Parcel and Letter Mail -- Recent Advances in Strategic and Tactical Planning of Distribution Subnetworks for Letter Mail -- Optimizing long-haul transportation considering alternative transportation routes within a parcel distribution network -- New approaches of realizing an optimized network -- A mixed integer programming approach to surgery scheduling with simultaneous decision making.
Keywords: Engineering economics; Engineering economy; Production management; Engineering Economics, Organization, Logistics, Marketing; Operations Management